Mathematical models for the study of Zika diffusion with exposed state and delay - Delgado Moya, Erick Manuel (2020)
Zika virus spreads to people primarily through the bite of an infected Aedes aegypti species mosquito. But it Zika can also be passed through sex from an infected to his or her sex partners and it can be spread from a pregnant woman to her fetus. Zika continues to spreading geographically to areas where competent vectors are present. Although a decline in cases of Zika virus infection has been reported in some countries, or in some parts of countries, vigilance needs to remain high. In this work, we present two mathematical models for the Zika diffusion by using (1) ordinary differential equations with exposed state and, (2) ordinary differential equations with delay (discrete), which is the time it takes mosquitoes to develop the virus. We make a comparison between the two modeling variants. Computational simulations is performed for Santa Ana, which is that is prone to develop the epidemic in an endemic manner.